Strength characteristics of unsaturated soils - Peh, Qing Li. (2010)
The shear strength property of unsaturated soil is of great concern to geotechnical engineers. The effective stress principle by Terzaghi (1936) governs the shear strength for saturated soil mechanics but it is not sufficient to describe the shear strength of unsaturated soil. For unsaturated soils, the two stress state variables that govern the shear strength are net confining pressure (-ua) and matric suction (ua-uw). These stress state variables are used in the extended Mohr Coulomb failure equation for unsaturated soil. The effects of matric suction forms the b component. In this report, the effects of matric suction and net confining pressure as stress state variables on the shear strength of unsaturated reclaimed sand are investigated using results from Constant Water content (CW) and Consolidated Undrained (CU) triaxial compression tests. The results showed that the effection friction angle,’ and the angle relating to matric suction, b for the sand are similar. The air entry value of the sand was found to be about 1.5 kPa and the initial matric suction range used in the tests was small, 0-25 kPa. Therefore net confining pressure is the dominant component affecting the shear strength in the tests.